2021
DOI: 10.1097/or9.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among patients with lymphoma: the association with personality and coping strategies

Abstract: Background: Up to one-quarter of patients with lymphoma experience persisting levels of psychological distress. This study aims to examine the extent to which personality traits and coping strategies, separately and together, are associated with psychological distress among patients with lymphoma, controlling for sociodemographic and clinical characteristics. Methods: A population-based sample of patients with lymphoma, selected from the Netherlands Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, the age of patients included in the study did not correlate statistically significant with GWB score. The same conclusion was formulated following the study of psycho-emotional distress in 456 patients with lymphoma in the Netherlands 22 . The authors concluded that younger patients experienced more psychological distress.…”
Section: Discussionmentioning
confidence: 67%
“…However, the age of patients included in the study did not correlate statistically significant with GWB score. The same conclusion was formulated following the study of psycho-emotional distress in 456 patients with lymphoma in the Netherlands 22 . The authors concluded that younger patients experienced more psychological distress.…”
Section: Discussionmentioning
confidence: 67%
“…focused on modifiable lifestyle factors or coping mechanisms). 27,[54][55][56] Additionally, it might also lead to improved symptom monitoring and better expectation management, which can help patients in making informed treatment decisions with their haematologist. [25][26][27] In conclusion, up to 10 years after diagnosis, patients with iNHL report a substantially lower HRQoL compared with an age-and sex-matched normative population.…”
Section: Discussionmentioning
confidence: 99%
“…This will not only improve early detection but will also enable us to develop tailored supportive care and treatment strategies for those in need (e.g. focused on modifiable lifestyle factors or coping mechanisms) 27,54–56 . Additionally, it might also lead to improved symptom monitoring and better expectation management, which can help patients in making informed treatment decisions with their haematologist 25–27 …”
Section: Discussionmentioning
confidence: 99%
“…Psychological distress is usually detected by measuring both anxiety and depression, and a high value of anxiety and/or depression is defined as high psychological distress ( Loge et al, 1997 ; Aksnes et al, 2007 ; ACTION Study Group, 2017 ; Arts et al, 2018 , 2021 ). Lack of detection of anxiety and depression has been shown to significantly affect the quality of life (QoL) and even increase mortality ( Cuijpers and Smit, 2002 ; Pinquart and Duberstein, 2010 ; Mols et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%